Recursos Interacionais Multimodais Mobilizados Por Uma Criança Com Transtorno Do Espectro Autista (Tea) Em Brincadeiras Familiares - Cots, Caroline Paola [UNIFESP] (2018)
This Research Wasdedicated To The Systematization, Description, And Analysis Of The Use Of Multimodal Interactive Resources Mobilized By A Child Diagnosed With Autistic Spectrum Disorder (Asd), Under The Pseudonym Luiza, During Familiar Everyday Situations In Which Spontaneous Play Emerged. Multimodal Interactional Resources Are Those Of A Distinct Semiotic (Goodwin, 2010), Verbal, Corporal And Material Nature, Mobilized By Participants During The Construction Of Their Linguistic-Interactive Practices. Our Interest Arose From The Description Of What Would Be Asd, Defined As A Condition That Affects Neurodevelopment Characterized, Among Other Things, By The Difficulty In Communication And Social Interaction, And By Restricted And Repetitive Behavior And Interests (Lai, Lombardo And Baron-Cohen, 2014). We Base Our Investigations On A Social Interaction Perspective Of Language Study On Asd (Ochs And Solomon, 2010, Sterponi, Kirby And Shankey, 2014, Sterponi And Kirby, 2015, Ochs, 2015), Which Has Shown That Many